Livelihood Assets and Income Generating Activities: A Comparative Analysis in the Scheduled and Non-Scheduled Areas of Jharkhand. Issue 3 (December 2021) - Sinha, Ashish Aman; Behera, Hari Charan; Behura, Ajit Kumar; Sahoo, Amiya Kumar; De, Utpal Kumar
The main objective of the article is to identify different types of livelihood assets, income generating activities (IGAs) and choices of these activities by households across social groups in the Fifth and non-Fifth Scheduled areas of Jharkhand in eastern India. It is based on a primary survey of 785 households randomly selected across caste and Scheduled Tribe groups in Giridih and Latehar districts of Jharkhand. K -means clustering is applied for determination of latent class activity clusters and Multinomial Logistic Regression (MLR) model used for understanding the importance of livelihood assets in determining livelihood activity cluster (LC) for income generation. Further, discriminant analysis is applied to obtain probability of choice of individual households in determining livelihood generating activity. The analysis shows that forest-based activity remains a better livelihood support system in the Fifth Scheduled areas, which is less significant and further diminishing in the non-Fifth Scheduled areas. Rural households engaged in a diverse set of IGAs to obtain additional income to reduce risk and maintain a balanced consumption. Occupational transition is marked by the decline of agriculture and increasing reliance on daily-wage activities as the primary source of income. Other traditional livelihood activities such as animal husbandry and the collection of forest produce have less scope for income in the absence of institutional support.